The Strategy for Handling the Impact of Covid-19 Pandemic by Sanur Tourism Actors - Putra, I Putu Angga Suta Pramana; Wiranatha, Agung Suryawan; Suryawardani, I Gusti Ayu Oka (E-Journal of Tourism, 2022)
The COVID-19 pandemic has given a negative impact on Sanur tourism, therefore a strategy for handling the impact of COVID-19 pandemic is needed for the restoration of Sanur tourism. This study aims to determine the strategies of tourism actors in handling the impact of COVID-19. This research uses a qualitative approach with a case study research strategy. The method used is observation, interviews, questionnaires and documentation. The theory used is perception theory to identify visitor perceptions and sustainable tourism theory to analyze the effectiveness of implementing strategies for Sanur tourism actors. The results show that the visitor's perception of the image of the Sanur destination is very good, it can be seen from the information received by visitors from Sanur tourism actors is clear, and the end understands the risks and threats when visiting so that visitors do not want to change their travel plans to Sanur. The strategies carried out by Sanur tourism actors are Reduction, Readiness, Response and Recovery. The effectiveness of implementing the strategy is seen from the environmental aspect, namely improving and rejuvenating the environment, the economic aspect of increasing tourist visits and the social aspect of growing awareness (awareness) of tourism actors and the community in the Sanur destination of the risks caused by disasters. The government and tourism actors need synergy in dealing with the impact of disasters on tourism so that they can help and speed up the handling process and minimize the negative impacts that arise. Keywords: tourism actors strategy; covid-19; tourism crisis.